Coping with Objectification: Female English Literature Students’ Physical Identity Development as Emerging Adults - Difa Mahya Zahara (IJELR: International Journal of Education, Language, and Religion, 2023)
Emerging adulthood is a stage where identity exploration is one of its developmental tasks. As most modern-age emerging adults participate in higher education, educational context becomes decisive in understanding their identity development, including the physical identity (body image) of female college students, especially considering the increasing participation of women in higher education which reflects the necessity to attend to their educational and developmental needs. This study draws qualitative data through a phenomenological study of four female college students of an Islamic university in an urban area of Indonesia, specifically the English Literature students. By applying the feminist theory of objectification and the concept of emerging adulthood, this study aims to understand how female college students experience objectification specific to their educational context and how it impacts their physical identity development as emerging adults. This study finds that objectification is experienced by female college students through the curriculum; learning contents, media, dress codes, and students-lecturers, students-peers, as well as students-staff relationships. The experiences indicate negative views of their physique during the college years reflected in negative subjective experiences (shame, anxiety, disrupted peak motivational states, and diminished awareness of internal bodily states), as well as eating disorder risks. However, an overall positive body image is observed in the current time once graduating which rather reveals a non-appearance-focused physical identity—physical health, comfort, and safety—achieved through contextual and reflective thinking. Thus, this study suggests the implication of college or higher education as a facilitator of emerging adults’ physical identity exploration.